SMU launches its first SkillsFuture Work-Study Degree to meet demand for software engineers - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
The School of Computing and Information Systems (SCIS) at the Singapore Management University will, from Academic Year 2022-2023 (which begins in August 2022), offer the University’s first work-study degree in software engineering to train a pipeline of talent with the necessary knowledge and skills to meet the demand for such talent.